1991
DOI: 10.1126/science.251.4997.1065
|View full text |Cite
|
Sign up to set email alerts
|

Salicornia bigelovii Torr.: An Oilseed Halophyte for Seawater Irrigation

Abstract: The terrestrial halophyte, Salicornia bigelovii Torr., was evaluated as an oilseed crop for direct seawater irrigation during 6 years of field trials in an extreme coastal desert environment. Yields of seed and biomass equated or exceeded freshwater oilseed crops such as soybean and sunflower. The seed contained 26 to 33 percent oil, 31 percent protein, and was low in fiber and ash (5 to 7 percent). The oil and meal were extracted by normal milling equipment, and the oil was high in linoleic acid (73 to 75 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
137
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(141 citation statements)
references
References 14 publications
2
137
0
2
Order By: Relevance
“…They could not find an explanation for the growth optimum at 300 mM NaCl. (Yeo and Flowers, 1980); (2) Salicornia dolichostachya (van Diggelen, 1988); (3) Salicornia bigelovi (Glenn and O'leary, 1984;Glenn et al, 1991); (4) Spartina alterniflora (Parrondo et al, 1978); (5) Spartina alterniflora (van Diggelen, 1988); (6) Aster tripolium (van Diggelen, 1988); (7) Beta vulgaris ssp. maritima (Rozema et al, 1993;Niazi, 2007); (8) Triticale and Barley (Hordeum vulgare) (Sajjad, 1983); Wheat (Triticum aestivum) (Francois et al, 1994).…”
Section: Salt Tolerance and The Spatial Distribution Of Halophytes Anmentioning
confidence: 99%
“…They could not find an explanation for the growth optimum at 300 mM NaCl. (Yeo and Flowers, 1980); (2) Salicornia dolichostachya (van Diggelen, 1988); (3) Salicornia bigelovi (Glenn and O'leary, 1984;Glenn et al, 1991); (4) Spartina alterniflora (Parrondo et al, 1978); (5) Spartina alterniflora (van Diggelen, 1988); (6) Aster tripolium (van Diggelen, 1988); (7) Beta vulgaris ssp. maritima (Rozema et al, 1993;Niazi, 2007); (8) Triticale and Barley (Hordeum vulgare) (Sajjad, 1983); Wheat (Triticum aestivum) (Francois et al, 1994).…”
Section: Salt Tolerance and The Spatial Distribution Of Halophytes Anmentioning
confidence: 99%
“…As a result, there is increasing interest in the development of productive uses for salt-affected agricultural land (Rozema and Flowers, 2008;Bennett et al, 2009). Much research has concentrated on the development of salttolerant crop and pasture plants for human consumption or livestock production (Glenn et al, 1991;Rogers et al 2005;Al-Shorepy et al, 2010;Norman et al, 2012; Pearlstein et al, 2012). Another productive option for salt-affected agricultural land is to use saline groundwater for aquaculture (Barson and Barrett-Lennard 1995;Forsberg et al, 1996;Doupé et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The plant is one of the halophyte species that has been 185 successfully utilized as a green fodder or hay in animals diet (Glenn et al, 1992;Swingel et al, 1996; Kraidees et al, 1998). Glenn et al (1991) evaluated the Salicornia i n extreme coastal desert environment and reported that the yield of seed and biomass were equal or exceeded the freshwater oilseed crops such as soybean and sunflower. The average crude protein, ether extract, ash and NaCl of Salicornia bigelovii biomass were 6.0%, 1.3%, 33.6% and 26.8%, respectively (Glenn et al, 1992).…”
Section: Introductionmentioning
confidence: 99%